সমাধান করি: \(\cfrac{a}{x-a}+\cfrac{b}{x-b}=\cfrac{2c}{x-c}, x\ne a,b,c\)


\(\cfrac{a}{x-a}+\cfrac{b}{x-b}=\cfrac{2c}{x-c} \)
বা, \(\cfrac{a}{x-a}+\cfrac{b}{x-b}=\cfrac{c}{x-c}+\cfrac{c}{x-c} \)
বা, \(\cfrac{a}{x-a}-\cfrac{c}{x-c}=\cfrac{c}{x-c}-\cfrac{b}{x-b} \)
বা, \(\cfrac{a(x-c)-c(x-a)}{(x-a)(x-c)} =\cfrac{c(x-b)-b(x-c)}{(x-c)(x-b)} \)
বা, \(\cfrac{ax-\cancel{ac}-cx+\cancel{ac}}{(x-a)}=\cfrac{cx-\cancel{bc}-bx+\cancel{bc}}{(x-b)} [∵x≠c]\)
বা, \(\cfrac{ax-cx}{(x-a)}=\cfrac{cx-bx}{(x-b)} \)
বা, \((ax-cx)(x-b)=(x-a)(cx-bx)\)
বা, \(ax^2-abx-cx^2+bcx=cx^2-bx^2-acx+abx \)
বা, \(ax^2-abx-cx^2+bcx-cx^2+bx^2+acx-abx=0\)
বা, \(ax^2+bx^2-2cx^2-2abx+bcx+acx=0 \)
বা, \(x(ax+bx-2cx-2ab+bc+ac)=0\)

∴হয় \(x=0\)
নয়, \(ax+bx-2cx-2ab+bc+ac=0 \)

যখন, \(ax+bx-2cx-2ab+bc+ac=0\)
তখন, \(ax+bx-2cx=2ab-bc-ac \)
বা, \(x(a+b-2c)=2ab-bc-ac\)
বা, \(x=\cfrac{2ab-bc-ac}{a+b-2c} \)

∴নির্ণেয় সমাধান, \(x=0\) অথবা, \(x=\cfrac{2ab-bc-ac}{a+b-2c}\)

Similar Questions